Markers of Venous Thromboembolism Risk in Patients with Alopecia Areata: Is There Anything to Worry about? - Anna Waśkiel-Burnat; Adriana Rakowska; Michał Zaremba; Magdalena Maciejewska; Leszek Blicharz; Michela Starace; Matilde Iorizzo; Bianca Maria Piraccini; Małgorzata Olszewska; Lidia Rudnicka (Adis, Springer Healthcare, 2023)
Abstract Background Numerous studies have indicated that alopecia areata is associated with a chronic systemic inflammation, which is considered as a risk factor for venous thromboembolism. The aim of the study was to evaluate the following markers of venous thromboembolism risk: soluble fibrin monomer complex (SFMC), thrombin-antithrombin complex (TATC), and prothrombin fragment 1 + 2 (F1 + 2) in patients with alopecia areata and compare them with healthy controls. Methods In total, 51 patients with alopecia areata [35 women and 16 men; mean age: 38 (19-54) years] and 26 controls [18 women and 8 men; mean age: 37 (29-51) years] were enrolled in the study. The serum concentrations of thromboembolism markers were measured using an enzyme-linked immunosorbent assay (ELISA) kit. Results An increased level of SFMC was detected in patients with alopecia areata compared with the controls [25.66 (20-34.86) versus 21.46 (15.38-29.48) µg/ml; p < 0.05)]. In addition, a higher level of F1 + 2 was observed in patients with alopecia areata in comparison with the control group [70150 (43720-86070) versus 38620 (31550-58840) pg/ml; p < 0.001]. No significant correlation was detected among SFMC or F1 + 2 and the Severity of Alopecia Tool (SALT) score, disease duration, or the number of the hair loss episodes. Conclusion Alopecia areata may be associated with an increased risk of venous thromboembolism. Regular screening and preventive management of venous thromboembolism may be beneficial in patients with alopecia areata, especially before and during systemic Janus kinase (JAK) inhibitors or glucocorticoid therapy.